2000
DOI: 10.1103/physrevlett.84.2393
|View full text |Cite
|
Sign up to set email alerts
|

Self-Amplification of Coherent Spontaneous Emission in a Cherenkov Free-Electron Maser

Abstract: Ultrashort pulses of microwave radiation have been produced in a dielectric-lined Cherenkov free-electron maser (FEM) amplifier. An intense initial seed pulse, due to coherent spontaneous emission (CSE), arises at the leading edge of the electron pulse. There is evidence to show that 3-4 cycle spikes are produced through the amplification of these seed pulses. A strong dependence of the start-up power on the rise time of the electron pulse has been found. The experimental results are verified by a theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Longer wavelength systems have demonstrated that bunch rise times $10k/c, where c is the speed of light in vacuum, are sufficiently rapid to seed self-amplified coherent spontaneous emission (SACSE) in FELs. 28,29 At k ¼ 150 nm, for example, this corresponds to a threshold rise time $5 fs. For our beam line setup as modelled in Fig.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…Longer wavelength systems have demonstrated that bunch rise times $10k/c, where c is the speed of light in vacuum, are sufficiently rapid to seed self-amplified coherent spontaneous emission (SACSE) in FELs. 28,29 At k ¼ 150 nm, for example, this corresponds to a threshold rise time $5 fs. For our beam line setup as modelled in Fig.…”
Section: Applied Physics Lettersmentioning
confidence: 99%
“…Since the radiation pulse occurs on short time scales less than the single pass transit time of the device, numerical noise has not been an issue for these simulations. SASE and superradiance initiated by CSE have been observed in the Cerenkov maser [7,21,22]. Using PIC simulations, we can extract parameters associated with both the linear and nonlinear regimes of operation.…”
Section: Transient Sase Pic Simulationsmentioning
confidence: 99%
“…Cerenkov masers are attractive sources of radiation at centimeter and millimeter wavelengths [2][3][4] and have demonstrated high power capabilities [5,6]. Cerenkov masers also have applications in short pulse microwave generation by the SASE mechanism as observed by Wiggins et al [7]. An excellent treatment of the general subject of beam-wave interaction can be found in the text by Schächter [8].…”
Section: Introductionmentioning
confidence: 99%
“…If ways are found to produce an electron bunch microstructure with Fourier components at the resonance frequency, a large stable 'spontaneous' coherent signal will act as an (intrinsic) injection source in the FEL amplifier (i.e. SACSE FEL; Wiggins et al 2000). This may be achievable using future laser-plasma accelerators because their predicted electron bunch durations can approach one femtosecond or less.…”
Section: Radiation Source Developmentmentioning
confidence: 99%